ViSTREET: An Educational Virtual Environment for the Teaching of Road Safety Skills to School Students - Chuah, Kee Man; Chen, Chwen Jen; Teh, Chee Siong (Springer-Verlag Berlin Heidelberg, 2009)
Virtual reality (VR) has been prevalently used as a tool to help students learn and to simulate situations that are too hazardous to practice in real life. The present study aims to explore the capability of VR to achieve these two purposes and demonstrate a novel application of the result, using VR to help school students learn about road safety skills, which are impractical to be carried out in real-life situations. This paper describes the system design of the VR-based learning environment known as Virtual Simulated Traffics for Road Safety Education (ViSTREET) and its various features. An overview of the technical procedures for its development is also included. Ultimately, this paper highlights the potential use of VR in addressing the learning problem concerning road safety education programme in Malaysia.